Self-assembly and coverage dependent thermally induced conformational changes of Ni(II)-meso-tetrakis (4-tert-butylphenyl) benzoporphyrin on Cu(111) - Zhang, Liang; Lepper, Michael; Stark, Michael Werner; Lungerich, Dominik; Jux, Norbert; Hieringer, Wolfgang; Steinrück, Hans-Peter; Marbach, Hubertus (Physical Chemistry Chemical Physics, 2015)
A systematic scanning tunnelling microscopy investigation of the self-assembly and of thermally induced conformational changes of Ni(II)-meso-tetrakis (4-tert-butylphenyl) benzoporphyrin (Ni-TTBPBP) on Cu(111) is presented. At room temperature, Ni-TTBPBPs diffuse on the surface and self-assemble into ordered islands with well-defined registry to the substrate, with two different azimuthal orientations. The formation of the characteristic supramolecular structure is attributed to van der Waals interactions between the tert-butyl groups. Upon moderate heating, the intramolecular conformation changes irreversibly due to a dehydrogenative intramolecular aryl-aryl coupling reaction. This reaction is coverage dependent, with a lower rate at higher initial coverage; this behaviour is attributed to a stabilization of Ni-TTBPBP in the ordered islands at higher coverage.